He Who Says Organisation Says Oligarchy and She Who Says Gender Says Woman: The Quest for Men’s Interest in Gender Studies - OLADIPO, Temidayo David; OLUGBEMI-GABRIEL, Olumide; OYENIYI, Toluwalope Olubukola; TOWOJU, Mercy Oyinkansola (The Gender Truth Journal, 2025)
This paper interrogates the gynocentric orientation of gender studies, arguing that its prevailing focus on women’s experiences has produced a harmful “single story” that marginalises male-specific burdens and diverse masculinities. Drawing on Robert Michels’s Iron Law of Oligarchy and critiques of exclusionary narratives, the study posits that the field frequently narrows the expansive concept of “gender” to exclusively denote “woman”. Employing a critical-analytical approach guided by the intersectionality framework, the research synthesises theoretical literature and lived-experience accounts to expose exclusionary practices. Our analysis demonstrates how this women-centred focus systematically occludes the study of diverse masculinities and male suffering, often relying on a reductive narrative that frames men primarily as oppressors and women as victims. The paper specifically highlights unique male burdens—such as elevated occupational risk, social role strain, suppressed emotional expression, and poorer help-seeking behaviour—that remain largely unexamined in mainstream scholarship. Furthermore, we show that formal and informal exclusionary practices within academic and activist communities discourage men from participating as researchers and interlocutors, thereby reinforcing narrow gynocentric epistemological boundaries. The conclusion is that a genuinely intersectional and reoriented gender studies, one that actively incorporates men’s perspectives and experiences, is crucial to strengthening the field’s explanatory power, reducing harmful single-story framings, and advancing collective strategies to address gendered injustices affecting all people.